Lojalność pracownika a ryzyko personalne firmy - Piórkowska-Wojciechowska, Katarzyna (Employee Loyalty and Personal Risk, 2005)
The article is a contribution to further discussion about the creation of employee loyalty in a turbulent environment. The author proves the existence of relationships between employee loyalty and personal risk. Results of contemporary research into social capital, loyalty, personal risk prove that these categories have influence on enterprise existence and development. But is the structure of social life based on loyalty indeed? Can loyalty degeneration lead to enterprise death?
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1089, s. 83-91